A Reflexive Approach to Israeli-Palestinian Encounter Groups: A New way of Conducting Dialogue Between Groups in Entrenched Conflict - Gil-Shuster, Corey (Université Saint-Paul / Saint Paul University, 2011)
This paper looks at why Israeli-Palestinian encounter groups have not been as successful as hoped by theory. Through the categorization of themes found in the literature and through experience of the writer, the core dynamics of encounter groups are analyzed. One of the key aspects missing in encounter groups is reflexivity: being able to see how what one does and says impacts the conflict and then being able to view the conflict from both sides’ perspectives. This paper lays out the design of an encounter group based on reflexivity. By learning about the dynamics that occur when Israelis and Palestinians meet in dialogue and using neutral conflict theory, temporarily removing the participants mentally from the conflict, participants can gain a better understanding of their own behaviour and the other’s behaviour. It is hoped that through a reflexive approach, participants will have better long term outcomes in terms of change in attitudes.
Keywords: Israel; Israeli; Palestinian; Arab; Jewish; dialogue; encounter groups; peace; reflexive